Jalan Tengah Indonesia Menuju Penghapusan Pidana Mati - Wie, Calvin (Jurnal Hukum & Pembangunan, 2025)
Constitutional Court Decision Number 2-3/PUU-V/2007 states that the death penalty does not conflict with the 1945 Constitution of the Republic of Indonesia. However, the decision provides a kind of guideline that suggests that efforts should be made to moderate the death penalty, including by removing the death penalty from the main criminal system and by formulating provisions for postponing the implementation of the death penalty (conditional capital punishment). This was followed up in the reform of the national criminal law with the promulgation of Law Number 1 of 2023 concerning the Criminal Code. This research aims to determine the legal ratio for postponing the implementation of the death penalty and the procedures for changing the death penalty to life imprisonment in Law Number 1 of 2023. The research results show that the provisions on the death penalty in Law Number 1 of 2023 are aimed at preventing the occurrence of waiting rows for the death penalty (death row) and at the same time, show the government's efforts to carry out as far as possible not the death penalty (abolitionist in practice).